1994
DOI: 10.1007/bf02265357
|View full text |Cite
|
Sign up to set email alerts
|

What are the relative steric demands of carboxyl and methyl groups?

Abstract: The relative steric demands of carboxyl and methyl groups are compared by contrasting the difference quantity 5 -~ AH~'(g, ArCOOH) -AH~'(g, ARCH3) for a collection of alkylated benzoic acids and toluenes with the value for Ar = C6H5, the archetypical (i.e., unsubstituted) benzoic acid and toluene. We conclude that carboxyl and methyl groups are nearly the same size.KEY WORDS: Benzoic acids; enthalpy of formation; isomers; toluenes.This brief note discusses the relative steric demands of two of the most impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 10 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…Roux, some of her Spanish coworkers (including her thesis advisor), and one of the current paper's authors showed [126] there was a nearly constant gas phase enthalpy of formation difference for alkylated benzoic acids and the corresponding toluenes in which COOH was replaced by CH 3 . We ask, then, does this near equality apply to the substituted benzoic acids in the paper by Vecchio? In the next paper, Miranda et al [127] reported a computational study using DFT to calculate the structure and energetics of 2-and 3-pyrrolidinone, tetrahydro-2-and -3-furanone, 2-, 3-, and 4-piperidinone, and tetrahydro-2-, -3-, and -4-pyranone.…”
Section: Issuementioning
confidence: 86%
“…Roux, some of her Spanish coworkers (including her thesis advisor), and one of the current paper's authors showed [126] there was a nearly constant gas phase enthalpy of formation difference for alkylated benzoic acids and the corresponding toluenes in which COOH was replaced by CH 3 . We ask, then, does this near equality apply to the substituted benzoic acids in the paper by Vecchio? In the next paper, Miranda et al [127] reported a computational study using DFT to calculate the structure and energetics of 2-and 3-pyrrolidinone, tetrahydro-2-and -3-furanone, 2-, 3-, and 4-piperidinone, and tetrahydro-2-, -3-, and -4-pyranone.…”
Section: Issuementioning
confidence: 86%
“…In an earlier study, Colomina et al [2] compared the energetics of alkylated toluenes and benzoic acids from which they concluded that the methyl and carboxylic acid functionalities were very similar, at least from the vantage point of gas phase enthalpies of formation and size. In this study, it was shown that the difference of the enthalpies of formation of an alkylated toluene and corresponding alkylated benzoic acid was nearly a constant; and therefore, it was concluded that the steric demand of these two groups was nearly the same.…”
mentioning
confidence: 98%